Evaluation of the Psychometric Properties of the Chinese Internet Gaming Disorder Checklist (C-IGDC) Among Chinese Adolescents - Chen, Juliet Honglei; Su, Xiaoyu; Dang, Le; Wu, Anise M. S. (Frontiers in Psychiatry, 2021)
As the first DSM-5 based, multidimensional screening tool of Internet gaming disorder (IGD) designed for Chinese gamers, the Chinese Internet Gaming Disorder Checklist (C-IGDC) has shown satisfactory psychometric properties among Chinese young adults. Given the high vulnerability to IGD among adolescents, the present study aimed to examine the applicability of C-IGDC to Chinese adolescents to address shortfalls in the existing literature regarding the assessment of adolescent IGD screening. Through a two-stage sampling method in a cross-sectional survey, we obtained a sample of 1253 Chinese past-year adolescent gamers (43.8% female; Mage = 14.49 years, SDage = 1.60 years) from local junior or senior high schools in Macao, China for data analysis. Our data confirmed a good model fit of the original two-level, nine-subfactor structure of the 27-item C-IGDC and found adequate internal consistency and test-retest reliability, as well as good concurrent validity as evidenced by expected associations with IGD functioning impairments, gameplay characteristics, and depressive symptoms. An optimal screening cutoff score (≥ 20) was proposed to identify probable disordered gamers among Chinese adolescents with past-year gaming experience. The findings support the extended use of C-IGDC to Chinese adolescents as a reliable and valid assessment tool for indicating IGD severity levels and screening for probable IGD cases. Its use can facilitate a proper screening procedure for probable IGD cases in both school and clinical settings.